PENGERINGAN BIJI KAKAO MENGGUNAKAN PLASTIK ULTRAVIOLET DAN PENENTUAN MUTU SESUAI STANDAR SNI - Ansharullah Ansharullah; Tamrin Tamrin; SrI Wahyuni; La Rianda La Rianda; Abdul Madiki; Andi Bahrun; Marsuki Iswandi; La Ode Nafiu; La Aba La Aba; Nur Salam (Universitas Mataram, 2023)
abstract